EFFICACY OF NEUROMUSCULAR THERAPY IN PATIENTS WITH CHRONIC LOW BACK PAIN (International Journal of Ayurveda and Pharma Research, 2017)
Low back pain (LBP) is a common musculoskeletal problem that is often chronic or recurrent. Myofascial trigger points (MTrPs) cause low back pain and are prevalent in patients with LBP. The aim of this study was to assess the effectiveness of multimodal treatment of MTrPs in patients with chronic low back pain. A single-assessor, blinded, randomized, controlled trial was conducted at Mannam Ayurveda Medical College, Pandalam. The intervention group received comprehensive treatment on alternate days consisting of trigger point releasing by manual compression of the MTrPs, stretching of the muscles and Dhanyamla dhara. Patients were instructed to perform muscle-stretching and relaxation exercises and maintain good posture. The control group was received only Dhanyamla dhara. The Oswestry Low Back Pain Disability questionnaire score (OLBPD) (primary outcome), Visual Analogue Scale for Pain (VAS-P), and the number of muscles with MTrPs were assessed at base line, 3 and 6 weeks in the intervention group and compared with those of a control group. As compared to the control group, the intervention group showed significant improvement (P < 0.05) on the OLBPD after 6 weeks. The results of this study show that 6-week comprehensive treatment of MTrPs in lower back muscles such as Piriformis, Quadratus lumborum, and iliopsoas muscles reduces the number of muscles with active MTrPs and is effective in reducing symptoms and improving Sciatica. IVDP can be prevented by early detection and deactivation of Myofascial trigger points. Combination therapy of trigger point releasing with Ayurvedic therapies shows highly beneficial in LBP.